The Road to Balance in Asia Pacific: Geopolitics of American Rebalancing and Chinese Belt and Road Initiative, Dr Atia Ali Kazmi - Ms. Amna Saqib (CISS Insight Journal, 2023)
The ancient Chinese philosophy of Yin-Yang does not look at different ideas or objects as opposites and mutually exclusive. Instead, it posits that they are connected at some level and contribute to each other’s strength and growth in the longer scheme of things. Application of this philosophy on establishment of relations between the United States and People’s Republic of China in the 1970s was the defining factor that has had far-reaching impact on the world politics, according to the author, Dr Atia Ali Kazmi. The US was then one of the poles in a bi-polar world order and China a potential great power, which had a dynamic economy in the past and could rise again. Both the states also had major stakes in the geopolitics of Asia Pacific region.